PEMETAAN DIGITAL UMKM DI DESA KEBONAGUNG MELALUI GOOGLE MY APPS - Alfarisi, Muhammad Adha; Salma, Rona; Prasetya, Oka; Arini, Roby; Aprilia, Rizka; Baihaki, Muhammad; Azidan, Muhammad Farhan; Nolan, Febrian; Nur, Muhammad Rizal; Salma, Razelfa Nabila; Yanti, Siska Dwi; Pebriansyah, Widia Nur (An-Nizam, 2025)
Kebonagung Village is one of villages in Tegalrejo Subdistrict, Magelang Regency, Central Java Province, covering an area of approximately 412 hectares consisting of agricultural land, plantations, and residential areas. Most of the population works in the agricultural and plantation sectors, as well as developing a variety of micro, small, and medium enterprises (MSME). According to Magelang Regency's Progress Data, there are 93 active MSME in Kebonagung Village operating in various fields, ranging from culinary, handicrafts, to agricultural product processing. However, the documentation of MSMEs has not been fully digitized, making it less supportive of village planning and the promotion of local potential. Through the 2025 Thematic Community Service Program (KKN), a UMKM mapping activity using Google My Maps was conducted. The data collection was carried out door-to-door by KKN students to obtain accurate and comprehensive data. The information collected includes the geographical location of MSME, business categories, products produced, prices, owner names, and product photo documentation. This data is then processed and visualized in the form of a digital map that can be accessed online, making it easier for village governments and business actors to promote, manage data, and plan village economic development. The methods used in this activity combine field surveys, primary data collection and digital data processing. The outcome of this activity is a digital map of SMEs in Kebonagung Village, which is expected to enhance the visibility of local products, expand marketing networks, and serve as a replicable model for other villages in Magelang Regency.